Comparison of clinical features and outcomes between two age groups of cryptorchidism testicular torsion in children: a retrospective study in single center - Wang, Shengxiong; Tang, Haohui; Zhang, Jingmin; Qiu, Ying; Xie, Xianghui (Frontiers in Pediatrics, 2024)
The purpose of this study was to compare the clinical characteristics and outcomes of children with cryptorchidism testicular torsion between the younger age group and the older age group .We collected the clinical data of children with cryptorchidism complicated with testicular torsion in our hospital from January 1, 2013 to January 1, 2023. The patients were divided into two groups: the younger age group (1month ~4 years old, n = 7) and the older age group (4 ~18 years old, n = 7). The differences of clinical manifestations and surgical results between the two groups were compared.A total of 14 patients with unilateral cryptorchidism testicular torsion were included in this study， including 9 on the left side and 5 on the right side. The main clinical manifestations were pain /swelling of groin. The rate of crying in the younger age group was significantly higher than those in the older age group [(5,71.4%) vs (0,0.0%), P＜0.05]. The median duration of symptoms of the younger group was less than the older group [42(7,96) h vs 70(24, 96) h, P＞0.05]. The ipsilateral testicular salvage rate in the younger age group was 14.3% (1/7), which was lower than the older age group 57.1% [(4/7), P＞0.05]. The degree of testicular torsion in younger age group was more severe than the older age group [720(360, 1080)°vs 360(270, 360)°, P＞0.05].The overall salvage rate of cryptorchidism testicular torsion is low. Although the duration of symptoms in the older age group was longer, the salvage rate of the older age group seemed to be higher than that in the younger age group. In addition, physical and imaging examination of the reproductive system should be carried out in time to identify the children with cryptorchidism testicular torsion in the early stage.